Pendidikan Kewarganegaraan Global: Urgensi dan Strategi membentuk Warga Global yang Inklusif.: Pendidikan Kewarganegaraan Global: Urgensi dan Strategi membentuk Warga Global yang Inklusif. - Anjar Sari, Fitria (Journal of Civics and Moral Studies, 2024)
This article attempts to present the urgency of learning themes in the context of global citizenship and strategies that can be implemented to form inclusive global citizens through global citizenship education. A global perspective is one of the main needs for contemporary citizens due to the increasing world problems whose solutions require interdependence and cooperation from all nations. Methodologically, this study uses a qualitative research approach with a case study research design with the research location at the Pancasila and Citizenship Education of study program, State University of Surabaya. The results of the study state that the urgency of learning themes that form global citizens is the concept of justice and equality, the concept of diversity and the concept of a sustainable environment while the strategy for forming knowledge, skills and attitudes of inclusive global citizens, by first, implementing a learning approach developed through curricular and organizational learning, second, developing an inclusive learning environment that has an impact on the formation of students' global knowledge and understanding, students' global skills and the development of students' global values. Keywords: global citizenship education, global citizens, inclusion